Adjacent Segment Degeneration After Anterior Cervical Discectomy and Fusion With an Autologous Iliac Crest Graft: A Magnetic Resonance Imaging Study of 59 Patients With a Mean Follow-up of 27 Years. Issue 6 (30th May 2017) - Burkhardt, Benedikt W; Simgen, Andreas; Wagenpfeil, Gudrun; Reith, Wolfgang; Oertel, Joachim M
Abstract: BACKGROUND: Anterior cervical decompression and fusion (ACDF) is a widely accepted surgical technique for the treatment of degenerative disc disease. ACDF is associated with adjacent segment degeneration (ASD). OBJECTIVE: To assess whether physiological aging of the spine would overcome ASD by comparing adjacent to adjoining segments more than 18 yr after ACDF. METHODS: Magnetic resonance imaging of 59 (36 male, 23 female) patients who underwent ACDF was performed to assess degeneration. The mean follow-up was 27 yr (18-45 yr). Besides measuring the disc height, a 5-step grading system (segmental degeneration index [SDI]) including disc signal intensity, anterior and posterior disc protrusion, narrowing of the disc space, and foraminal stenosis was used to assess the grade of adjacent and adjoining segments. RESULTS: The SDI of cranial and caudal adjacent segments was significantly higher compared to adjoining segments ( P < .001). The disc height of cranial and caudal adjacent segments was significantly lower compared to adjoining segments ( P < .001, P < .01). The SDI of adjacent segments in patients with repeat cervical procedure was significantly higher than in patients without repeat procedure ( P = .02, P = .01). The disc height of the cranial adjacent segments in patients with repeat procedure was significantly lower than in patients without repeat procedure ( P = .01). CONCLUSION: The physiological aging of the cervical spine does not overcome ASD. The disc height and the SDI in adjacent segment are significantly worse compared to adjoining segments. Patients who underwent repeat procedure had even worse findings of disc height and SDI.